Effect of COVID-19 Pandemic on Global Stock Market Values: A Differential Analysis: Array - Ngwakwe, Collins C (Acta Universitatis Danubius. Œconomica, 2020)
This paper presents a current analysis of the effect of coronavirus pandemic on select global stock indexes (SSE Composite Index [China], Euronext 100 [Europe], Dow Jones Industrial Average [United States of America]. The objective of the paper is to evaluate the extent and direction of the differential effect of COVID-19 pandemic on select world stock index. The data on stock value performance were gathered for fifty days before and fifty days within the Coronavirus epidemic; data were analysed using the paired t-test of difference in mean stock values at an alpha level of 0.05(5%). The results reveal that the COVID-19 pandemic has different effects on the stock markets. Dow Jones Industrial Average showed a significant reduction in mean stock value during the coronavirus period, Chinese Stock Exchange Composite Index experienced a significant increase in mean stock values during epidemic higher than before the epidemic. On the contrary, the S&P 500 and the Euronext 100 indexes show a non-significant difference in mean stock price. The paper provides direction to stock market participants, investors and speculators regarding a safer investment destination during this time of COVID-19 pandemic; the paper serves a good case study for class room teaching and also provides direction for further research. This paper provides the first empirical research on the early effect of COVID-19 pandemic on three global important regional stock indexes, which finds that some stock markets such as the Shanghai Composite Index is resilient to COVID-19 pandemic.